Elucidation of the mechanism of action of Δ9-tetrahydrocannabinol derivatives from Cannabis sativa for the potential treatment of multiple sclerosis by computational methods - Vasilić, Đorđe; Erić, Slavica (Archives of Pharmacy, 2022)
Multiple sclerosis (MS) is a disease in which demyelination, neurodegeneration and gliosis occur in the central nervous system. Some constituents of Canabis sativa (CS) extracts are known to have positive effects on symptoms, reduction of progression and healing of MS, whilst roles of particular constituents in extract are not fully elucidated. Late studies show 565 constituents of CS extracts presented and divided in 11 chemical groups. The aim of this study is the investigation of physico-chemical parameters of Δ9-tetrahydrocannabinol derivatives for further elucidation of their potential effect in treatment of MS. Structures building and geometry optimization were performed by ChemDraw Ultra 8.0 and Chem3D Pro 8.0, whilst descriptors were calculated using MarvinSketch and Codessa software. All 15 Δ9-tetrahydrocannabinol derivatives showed lipophilicity in wide range (logP from 4.71 to 12.01), which indicates specific mechanism of resorption and bioavailability, including various roles in potential reparation of myelin sheath. Steric parameters indicate wide range of energies of conformation in specific orientation of ligands and additional factors in potentially synergistic action of derivatives in distribution between agonistic and antagonistic action, as well as signalization and modulation of cannabinoid receptors. The presence of ester group in 8 derivatives of tetrahydrocannabinol implies possible role of acyl residues in reparation of myelin sheath. Results could serve as basis for further elucidation of roles of Δ9-tetrahydrocannabinol derivatives among synergistic engineering of full extract in potential treatment of MS, which concernes both relieving symptoms and healing MS, for which certain levels of evidence exist on human models.